Inhibitory influence of the dorsal nucleus of the lateral lemniscus on binaural responses in the rat's inferior colliculus - Li, L (J Neurosci, 1992)
The contribution of the dorsal nucleus of the lateral lemniscus (DNLL) to binaural processing was examined by recording single-unit activity in the rat's inferior colliculus before, during, and after a reversible block of the excitatory activity in DNLL by local injection of kynurenic acid. Recordings were made from the central nucleus of the inferior colliculus with glass micropipettes filled with 3 M sodium acetate. Kynurenic acid (2 mM in Locke's solution) was injected into the DNLL through one side of a double-barreled glass pipette. The other side of the pipette was filled with Locke's solution for making control injections and recording neural activity. Pressure injection of 0.7–2.0 microliter of kynurenic acid resulted in the complete cessation of tone- evoked responses in DNLL for periods of 45 min to 1 hr. Tone bursts were delivered separately to the two ears through headphones fitted to the external auditory meatus. Binaural responses in the inferior colliculus were determined by comparing the effects of monaural and binaural stimulation. Attention was focused on neurons that were excited by contralateral stimulation and inhibited by ipsilateral stimulation. Interaural intensity difference (IID) functions were generated by holding contralateral sound pressure constant at 10 dB above threshold while increasing ipsilateral sound pressure level. Prior to kynurenic acid injection, ipsilateral stimulation caused a pronounced suppression of contralaterally evoked single-unit activity. Unilateral injection of kynurenic acid into DNLL reduced the strength of binaural suppression in the contralateral inferior colliculus. In every cell tested, the IID curve in inferior colliculus was shifted following contralateral DNLL injection. The IID curve returned to normal after recovery of neural activity in DNLL. In contrast, no effect was seen in the inferior colliculus ipsilateral to the kynurenic acid injection. The injection of Locke's solution into DNLL had no effect on IID curves in the inferior colliculus. These data suggest that the DNLL plays a role in binaural processing through an inhibitory influence on responses in the contralateral inferior colliculus.